O comércio intra-setorial e suas aplicações para a economia cearense - Avelino, Gisela Maria Prata (2006)
This study aimed to evaluate the participation of intra-sectorial commerce in the state do Ceará exportation results, and its impacts on the main economic variables, from 1996 to 2004. The intensity of this type of commercial transactions were identified, based on the index considered for Grubel and Lloyd (1975). Then, its contribution on the total flow of internationally commercialized merchandises was evaluated, based on the methodology proposed for Menon and Dixon (1996). The analysis of the data shows that intra-sectorial commerce have a small contribuition on total commerce results and, despite some primary products and minerals partipate, the main commercialized products from the intra-sectotial commerce are manufactures. In relation to its impacts on the main economic variable, it was verified thar intra-sectotial commerce has positive effects on the generation of new jobs, however its intensification can provoke increases in the concentration of exportation guideline and in the level of income, while reduces the degree of commercial aperture of the State. It was also verified that, statistically, this type of commerce did not show significant effect in the industrialization degree of state of Ceará.